Insulinoma in a teenager with seizures - Hamzeh sherafati; Marjan Joodi; Mehdi Fathi; Mohammad Aref Emami; Leila Ameri; Pegah Bahrami Taqanaki; Mohammad Mehdi Zarif Soltani; Alireza Ghodsi; Mahdi Parvizi Mashhadi (Elsevier, 2022)
Insulinoma is an extremely rare pancreatic neuroendocrine tumor that originates from insulin-secreting islet cells, with an incidence of one to four cases per million each year. Here, we report a case of a 16-year-old boy presenting with seizures who was diagnosed with insulinoma and successfully treated with surgical resection.